Stratified dynamic analysis reveals postoperative recovery trajectories of sacral neuromodulation in pediatric neurogenic bladder - Ding, Yiming; Wang, Dongming; Wang, Pengxiang; Cheng, Fangzheng; Mou, Yaru; Zhou, Yu; Xin, Pengge; Niu, Zeyong; Wang, Jian (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the effectiveness and safety of sacral neuromodulation (SNM) under general anaesthesia in the treatment of neurogenic bladder (NB) in children, and to share clinical experience.MethodsWe conducted a retrospective analysis of the clinical data of 61 children with neurogenic bladder (NB) who successfully underwent sacral neuromodulation (SNM) treatment at Qilu Hospital of Shandong University from January 2021 to January 2025, with mid-term follow-up (up to 3 years). By tracking key indicators (such as symptomatology and urodynamic parameters) over an extended period, we assessed the safety and efficacy of SNM under general anesthesia for the treatment of pediatric NB and identified general patterns of postoperative recovery.ResultsPreoperatively, all 61 children exhibited symptoms of urinary frequency, urgency, and incontinence. After permanent SNM implantation, compared to baseline, symptoms of voiding dysfunction, including urinary frequency, incontinence, and urinary retention, were significantly alleviated. Urodynamic parameters, including detrusor pressure during the storage phase, bladder compliance, and maximum bladder capacity, also showed statistically significant improvements (P < 0.05). Through mid-term follow-up, we modeled postoperative recovery curves using mathematical methods such as restricted cubic splines, and sensitivity analyses confirmed their reliability. Based on these models, subgroup analysis further revealed that the recovery of urinary retention symptoms exhibited different patterns across subgroups.ConclusionSacral neuromodulation (SNM) under general anesthesia is a safe and reliable treatment for pediatric patients. Both early and mid-term postoperative care play a crucial role in optimizing recovery and ensuring sustained therapeutic efficacy.